Secure Coding in Five Steps - Mini Zeng; Feng Zhu (Journal of Cybersecurity Education, Research & Practice)
Software vulnerabilities have become a severe cybersecurity issue. There are numerous resources of industry best practices available, but it is still challenging to effectively teach secure coding practices. The resources are not designed for classroom usage because the amount of information is overwhelming for students. There are efforts in academia to introduce secure coding components into computer science curriculum, but a big gap between industry best practices and workforce skills still exists. Unlike many existing efforts, we focus on both the big picture of secure coding and hands-on projects. To achieve these two goals, we present five learning steps that we have been revising over the last four years. Our evaluation shows that the approach reduces complexity and encourages students to use secure coding practice in their future projects.